2013
DOI: 10.1111/cen.12078
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism of interleukin‐6 gene is related to plasma adrenomedullin levels

Abstract: Plasma ADM levels are related to the SNP rs17147230 in IL6 gene. The effect of the polymorphism on inflammation and cardiovascular disease remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The rs1800796 SNP is located in the IL-6 promoter and has been thought to be associated with adult TB in Chinese population recently [9]. The tag-SNP rs17147230 was thought to be functionally associated with plasma adrenomedullin levels by one research group [18]. Meanwhile, 10 tag-SNPs of IL-6R were included in our genotyping.…”
Section: Resultsmentioning
confidence: 99%
“…The rs1800796 SNP is located in the IL-6 promoter and has been thought to be associated with adult TB in Chinese population recently [9]. The tag-SNP rs17147230 was thought to be functionally associated with plasma adrenomedullin levels by one research group [18]. Meanwhile, 10 tag-SNPs of IL-6R were included in our genotyping.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical [ 42 44 ] and clinical data [ 45 ] point towards a modulating effect of ADM on IL-6 under different inflammatory conditions. Furthermore, plasma ADM levels have been found to be related to a single nucleotide polymorphism of the IL6 gene [ 46 ]. In the present study, we observed that addition of IL-6 to the multivariable model attenuated the association between MR-proADM and all-cause mortality, although the association remained significant.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, circulating AM levels could be modified by mutations in other genes; such as an exonic insertion/deletion polymorphism in an intermedin gene [38], a SNP in IL-6 gene [39], or a SNP in adiponectin gene [40]. Interestingly, the carriers of these mutations show a higher genetic predisposition to develop some pathologies related to AM such as hypertension, renal dysfunction, dysglycemia, or even cerebrovascular disease.…”
Section: Adrenomedullin Synthesis Release and Metabolismmentioning
confidence: 99%